Law Enforcement Against Elections Crime During Electoral Campaign 2019 (Case Study In Bawaslu of Banjarmasin City) - Sri Herlina; Umar Ma’ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Simultaneously in the general election in 2019 in London Election alleged criminal offense, whether it was exposed by the media and is still a byword society is becoming Bawaslu obligation to respond. Among them led to the process in Bawaslu Gakkumdu of Banjarmasin city whether it is a public report and findings by Bawaslu of Banjarmasin own. The cases that occurred not only before the campaign period, even at this stage that this time period campaign legalized legislative candidates for creativity lure the support of the constituency, also saw various criminal cases of elections. Though political parties have been briefed by Bawaslu of Banjarmasin about what and things that are prohibited during the campaign period and to explain and analyze: the factors that hinder and solutions for Bawaslu of Banjarmasin to enforce laws against criminal acts during the election campaign in 2019. This study is a sociological juridical data obtained in this study were analyzed by inductively qualitative descriptive method. The results of this study are: Factors that inhibit Bawaslu of Banjarmasin in enforcing the law against Crime Elections in Future Campaign in London on Election Unison 2019 is a factor of legal norms, budgetary factors, human resource factors and factors of the facility, then the solutions to the barrier is to maximize prevention efforts and strengthen budgeting, HR recruitment and complement facilities of Bawaslu of Banjarmasin.Keywords: Law Enforcement; Election Crime; Bawaslu of Banjarmasin.